A Polyphenylene Support for Pd Catalysts with Exceptional Catalytic Activity1. Issue 33 (15th July 2014) - Wang, Feng; Mielby, Jerrik; Richter, Felix Herrmann; Wang, Guanghui; Prieto, Gonzalo; Kasama, Takeshi; Weidenthaler, Claudia; Bongard, Hans‐Josef; Kegnæs, Søren; Fürstner, Alois; Schüth, Ferdi
Abstract We describe a solid polyphenylene support that serves as an excellent platform for metal‐catalyzed reactions that are normally carried out under homogeneous conditions. The catalyst is synthesized by palladium‐catalyzed Suzuki coupling which directly results in formation of palladium nanoparticles confined to a porous polyphenylene network. The composite solid is in turn highly active for further Suzuki coupling reactions, including non‐activated substrates that are challenging even for molecular catalysts.